Спонтанна флора Національного ботанічного саду імені М.М. Гришка НАН України (м. Київ). Повідомлення 1. Аборигенні види - Shynder, O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to study the species composition and structure of spontaneous flora in M.M. Gryshko National Botanical Garden of the NAS of Ukraine (Kyiv). Material and methods. The study was conducted in 2010–2018 on the territory of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Results. A summary of the indigenous fraction of the spontaneous flora of the M.M. Gryshko National Botanic Garden consisting of 385 taxa, is about 59 % of the total studied flora. 7 species, including rare ones, should be con sidered to have disappeared from the natural flora of the Botanical garden. Populations of several rare local flora species exist today and their conservation are important. Conclusions. The indigenous fraction of the spontaneous flora of Botanical garden includes relatively many species. The great landscape diversity of the Botanical garden with natural ecotops for such a state of flora is important, as well as the general species richness of the surrounding ecosystems in the region. The nature protection role of the M.M. Gryshko National Botanic Garden is extremely important, as indigenous flora of the RightBank of ForestSteppe is preserved on its territory. In the future repatriation of the lost populations of several disappeared rare in digenous species will be promising here.